Seroprevalence of melioidosis in sheep and goats from selected small ruminant farms in Selangor, Malaysia - Hambali, Idris Umar (Nexus Academic Publishers, 2018)
This study was designed to investigate the seroprevalence of Melioidosis in sheep and goats from selected small ruminant farms in Selangor, Malaysia. Blood samples (n=100) were collected each from sheep and goats using a random sampling technique from these farms. The serum samples were subjected to Melioidosis antibody screening using the Complement Fixation Test (CFT). The overall prevalence of Melioidosis among goats and sheep from these farms were 1% and 0%, respectively. It is concluded that although the prevalence of positive detection is low, there is need for further diagnostic surveillance as this singular case can be a potential reservoir for zoonotic infection.